Suspended sovereignty as a result of the Apostille Convention: Legal review of Article 1337 of the Civil Code - Kory Febrina Lestari Pardede; Eddy Pratomo; Tetti Samosir (Journal Evidence Of Law, 2025)
This study examines the risk of suspended sovereignty as a consequence of the ratification of the Apostille Convention in Indonesia from the perspective of Article 1337 of the Civil Code. The apostille system accelerates the legalization of foreign public documents, including international contracts, but reduces the substantive oversight function of Indonesian authorities. As a result, foreign documents that are formally valid and have obtained an apostille can still be recognized in Indonesia, even though they contradict national legal norms as stipulated in Article 1337 of the Civil Code. This condition creates a legal vacuum that weakens the practice of protecting national norms, so that substantive filtering can only be carried out after the document becomes a source of dispute. The research results recommend the urgency of a complementary mechanism in the form of regulations and substantive testing so that global administrative efficiency remains in line with the principles of legal sovereignty and the integrity of Indonesian values amid the tide of globalization of agreements.